Synthesis of ZnO/NiO/g-C3N4 Nanocomposite Materials for Photocatalytic Degradation of Tetracycline Antibiotic - Nong, Linh X.; Nguyen, Oanh Thi Kim (Masyarakat Katalis Indonesia - Indonesian Catalyst Society (MKICS), 2023)
In this study, an approach was utilized to improve the photocatalytic efficacy of g-C3N4 by creating a composite photocatalyst through co-precipitation. This process involved incorporating NiO and ZnO into the structure, resulting in enhanced photocatalytic activity. The Scanning Electron Microscopy (SEM) showcases interesting aggregation behavior, revealing extensive arrays of ZnO/NiO/g-C3N4 particles. Ultraviolet–Visible Diffuse Reflectance Spectroscopy (UV-Vis DRS) confirms the composite's strong light absorption, especially in the visible spectrum. X-ray diffraction (XRD) analysis provides conclusive evidence of successful material synthesis. The degradation of tetracycline antibiotics under visible light exposure demonstrates an impressive photochemical degradation efficiency of 78.43%. Additionally, the composite exhibits impressive cycles of reuse, retaining its high photocatalytic activity even after four reaction cycles. This performance surpasses that of comparison samples. The synergistic integration of NiO and g-C3N4 within ZnO proves to be crucial in enhancing photocatalytic activity by enhancing electron-hole separation and mitigating recombination processes. This composite photocatalyst shows a wide potential for efficiently eliminating tetracycline antibiotics from water systems. Copyright © 2023 by Authors, Published by BCREC Group. This is an open access article under the CC BY-SA License (https://creativecommons.org/licenses/by-sa/4.0).